Bamboo-based activated carbon for supercapacitor applications - Yang, Cheol-Soo; Jang, Yun Su; Jeong, Hae Kyung (Current applied physics, 2014)
Bamboo-based activated carbon is synthesized by a simple heat treatment with or without KOH activation, and characterized for possible energy storage applications. The KOH activation introduces a very large surface area of more than 3000 m2 g−1 to the bamboo-based activated carbon, resulting in high specific capacitance, energy density, and power density in an aqueous electrolyte. The specific capacitance retention is more than 91% of the original capacitance after 3000 cycles, proving excellent cyclic stability for supercapacitor applications. Our results indicate that the natural resource of common bamboo could be an essential raw material for the energy storage devices. [Display omitted] •Synthesis of bamboo-based activated carbon.•Enhanced surface area of more than 3000 m2 g−1 of the obtained activated carbon.•Excellent specific retention after 3000 cycles.•High specific capacitance from the obtained samples.